PENGARUH DISIPLIN KERJA, KEPUASAN KERJA, DAN KOMPETENSI DIGITAL TERHADAP KINERJA GURU SMP NEGERI SE-KABUPATEN MESUJI DENGAN BUDAYA SEKOLAH SEBAGAI MEDIASI - Narti Cikita Dewi; Tri Joko Raharjo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze, test, and empirically describe the direct influence of Work Discipline (X1), Job Satisfaction (X2), and Digital Competence (X3) on Teacher Performance (Y). In addition, this study examines the effect of those three independent variables on School Culture (Z) and the role of School Culture in mediating the relationship between the independent variables and Teacher Performance at public junior high schools in Mesuji Regency. This research employed a quantitative approach. The population consisted of 544 teachers, while the sample of 231 respondents was determined using a proporsional cluster random sampling technique. Data were collected through questionnaires using a Likert scale. The data analysis included Descriptive and Inferential Analyses, such as instrument tests, classical assumption tests, multiple linear regression, F test, t test, and path analysis. The results of the study show that Work Discipline, Job Satisfaction, Digital Competence, and School Culture partially have a positive and significant effect on Teacher Performance. Work Discipline, Job Satisfaction, and Digital Competence also have a positive and significant effect on School Culture. However, School Culture does not significantly mediate the effect of Work Discipline, Job Satisfaction, and Digital Competence on Teacher Performance. Therefore, the direct influence of the three independent variables on Teacher Performance is greater than their indirect effect through School Culture.